Pengaruh Locus of Control dan Intention to Act Terhadap Responsible Environmental Behavior Siswa SMA di Bekasi - Intan Puspita Sari (Universitas Negeri Jakarta, 2023)
Environmental problems have always been a hot topic discussed in the world. This is due to human behavior that tends to be bad. One effort to overcome this is to apply awareness and concern for the environment to students. Students as agents of change are expected to have responsible environmental behavior. Based on these problems, the purpose of this research was to determine the effect of locus of control and itention to act on responsible environmental behavior of high school students in Bekasi. This research was conducted at SMAN 18 Bekasi in the odd semester of the 2022/2023 with a research sample of 75 students. The method used is a survey method through casual studies and analyzed by path analysis. The results of calculation the reliability coefficient of responsible environmental behavior instrument is 0.898, intention to act is 0.933 and locus of control is 0.915. The results of this study are that locus of control has a direct effect on intention to act, intention to act has a direct effect on responsible environmental behavior, locus of control has a direct effect on responsible environmental behavior, locus of control has an indirect effect on responsible environmental behavior through intention to act.